Degradation efficiencies of 2,4,6-TCP by Fe.sup.0-based advanced oxidation processes with common peroxides - Ai, Luoyan; Ren, Tiancheng; Yan, Qin; Wan, Mengdan; Peng, Yajuan; Xu, Xiaoyun; Liu, Xinxin (PloS one, 2021)
Degradation of 2,4,6-trichlorophenol (2,4,6-TCP) by zero-valent iron (ZVI) activating three common peroxides (peroxymonosulfate (PMS), hydrogen peroxide (H.sub.2 O.sub.2 ), and peroxydisulfate (PS)) was investigated. The effects of ZVI dosage, peroxides concentration, initial pH, and Cl.sup.- concentration were examined. The 2,4,6-TCP degradation efficiencies by Fe.sup.0 /peroxides (PMS, H.sub.2 O.sub.2, PS) were compared. Results showed that the order for degradation efficiency was H.sub.2 O.sub.2 [greater than or equal to]PMS>PS. The degradation efficiency of 2,4,6-TCP in ZVI/peroxides systems were optimal at c(Ox) = 1 mmol*L.sup.-1 ; c(Fe.sup.0) = 0.1 g/L; initial pH = 3.2. Additionally, pH had a vital effect on 2,4,6-TCP degradation. At pH<3.2, ferrous play a vital role in all reaction, and accelerate the reaction rate rapidly. The existence of NaCl showed different results in the four systems. Chloride had little effect on 2,4,6-TCP degradation when chloride concentration at 5 mM, whereas the presence of 300 mM chloride significantly accelerated the degradation of 2,4,6-TCP from 72.7% to 95.2% in ZVI-PMS system. Notably, the other three systems showed opposite results. In contrast, the AOX (Absorbable Organic Halogen) values were highest in ZVI-PMS-Cl.sup.- system, due to the formation of lots of refractory chlorinated phenols as identified by GC-MS. These findings are good for choosing the most suitable technology for chlorophenol wastewater treatment.